Removal of lead and cadmium from aqueous solution by using cashew gum polysaccharide (Arabinogalactan) - Acrylamide hydrogel - ThweSoe, Aye Thwe; Khine, May Myat (Researcher and Lecturer Society, 2024)
There is an increasing need for clean water for human health and the environment, so the removal of toxic metals from wastewater with low-cost adsorbents plays an essential role. In this research, the synthesis of cashew gum (CG) polysaccharide (arabinogalactan)-acrylamide (Am) (CG-AM) hydrogel was carried out with three independent variables: Hydration ratio (ml/g), amount of monomer (acrylamide, Am) (g) and concentration of crosslinker (methylene-bisacrylamide, MBA) (%) by radical polymerisation. The removal efficiency of Pb2+ and Cd2+ from the stock solution of lead nitrate and cadmium sulphate by adsorption technique was also studied by optimisation using BBD of RSM. Furthermore, the functional and structural properties of all types of hydrogels were analysed by characterisation with FTIR, (XRD), (SEM) with EDS and swelling capacity analysis. An optimum hydrogel yield of 4.527 g was obtained at a hydration ratio of 10 ml/g, monomer amount of 2.5 g and crosslinker concentration of 3% w/v of one gram of extracted arabinogalactan. For Pb2+ removal, 86.985 % removal efficiency was obtained at a hydration ratio of 25 ml/g, monomer amount of 1g and crosslinker concentration of 1%, while for Cd2+ removal, 18.875 % removal efficiency was obtained at a hydration ratio of 10 ml/g, monomer amount of 4g and crosslinker concentration of 2%. (CG-AM)H Pb2+ had the highest swelling capacity of 11.072 g H2O/g polymer hydrogel but (CG-AM)H had the lowest of 5.322 g H2O/g polymer hydrogel due to crosslinking capacity. The FTIR result, the (CG-AM)H Pb2+ showed a significant peak of C-O stretching of the S-glycosidic bond of hydrogel to absorb the Pb2+ ions. From XRD and SEM results, (CG-AM)H Pb2+ showed an amorphous nature of hygroscopic properties and a three-dimensional network structure with open pores.